Association of Physical Fitness With the Risk of Atrial Fibrillation: A Systematic Review and Meta‐Analysis. Issue 7 (13th May 2016) - Zhu, Wengen; Shen, Yang; Zhou, Qiongqiong; Xu, Zhenyan; Huang, Lin; Chen, Qi; Hong, Kui
ABSTRACT: Several studies have investigated the role of physical fitness in atrial fibrillation (AF), but the results remain controversial. We aimed to estimate the association between physical fitness and risk of AF. We comprehensively retrieved data from the Cochrane Library, PubMed, and Embase databases until February 29, 2016, for studies evaluating the association of physical fitness with the risk of AF. Data were abstracted from included studies, and effect estimates were pooled using a random‐effects model. Six studies with a total of 205 094 participants and 15 919 AF cases fulfilled the inclusion criteria. When physical fitness was assessed as a continuous variable, per incremental increase of physical fitness was associated with a 9% reduced risk of AF (risk ratio [RR]: 0.91, 95% confidence interval [CI]: 0.84‐1.00, P = 0.05). When physical fitness was assessed as a categorical variable, the risk of AF was significantly reduced (RR: 0.51, 95% CI: 0.28‐0.91, P = 0.02) in individuals with the highest level of physical fitness compared with those with the lowest level. The intermediate vs the lowest level of physical fitness was associated with a 28% reduced risk of AF (RR: 0.72, 95% CI: 0.56‐0.93, P = 0.01). The sensitivity analysis indicated that these results were stable. Notably, there was evidence of statistical heterogeneity across studies; therefore, we should interpret the results cautiously. In conclusion, published literature supports that a higher level of physical fitness is associated with a lower risk of AF. Further studies should be performed to confirm these findings.